Experimental Study of Strengthening an RC Bridge Deck by Adding a Concrete Overlay. (26th July 2013) - Theiner, Y.; Hart, H.; Drexel, M.; Hofstetter, G.
ABSTRACT: The present contribution focuses on the experimental investigation of moisture distribution profiles of a reinforced concrete bridge deck determined before, during and after adding a concrete overlay. By means of a non‐destructive system, the mass water content distributions were measured in the existing bridge deck as well as in the concrete overlay. Furthermore, the in situ measurements were accompanied by a comprehensive laboratory test programme. Water desorption isotherms and ultimate drying shrinkage strain were determined on specimens made of both the substrate and overlay concrete. Moreover, moisture distributions and shrinkage strains were measured on concrete prisms stored under uniform climatic conditions. Comparison of in situ measurements with lab test results allows a better understanding of the impact of environmental influences on the bonded overlay behaviour. Comparison of in situ measurements with previous lab test results allows the assessment of the effectivity of surface preparation by high‐pressure water jetting and, hence, the examination of the significance of results from composite lab tests for real bridge decks strengthened by overlays. A comparison of an experimental and numerical study of restraint effects exerted from the substrate concrete on the overlay will be presented in an accompanying paper.